A study to assess the outcome of critically ill children with hypoalbuminemia admitted in a tertiary care center - Lakkappa, Lakshmi; Penta, V Bharathi Tulasi (Indian Journal of Child Health, 2018)
Introduction: Albumin is a major plasma protein, constituting around 55% of total protein load of the plasma. Hypoalbuminemia is commonly found in patients with heart failure, cirrhosis, nephrotic syndrome, severe malnutrition, thermal injuries, and protein-losing enteropathy. Objectives: The objectives of the study were to assess the outcome of critically ill children with hypoalbuminemia admitted in a tertiary care center. Materials and Methods: A total of 80 patients, who were diagnosed to be having hypoalbuminemia, were admitted in the pediatric intensive care unit (PICU) in Bengaluru. 80 patients with similar characteristics to cases and with normal levels of serum albumin were included in the study as “controls.” The study was undertaken over the duration of 1 year. Results: The mean serum albumin in cases at admission was 2.5±0.5 mg/dl and in controls was 4.3±0.6 mg/dl. Mean length of PICU stay among cases was 7.8±5.1 days and among controls was 5.1±3.2 days (p<0.001). Among cases 32.5% died and 67.5% survived, similarly among controls 35% died and 65% survived (p=0.73). Conclusion: The level of albumin in the children plays a very important role in determining the treatment options and the outcome of the treatment in the form of an increased rate of mortality and morbidity.